Ablation-resistant, high-efficiency, heat-insulating, room-temperature-vulcanized silicone rubber foam and preparation method thereof

By controlling assembly and silanization modification of ceramic fillers, combined with efficient mixing technology, the problem of excessive addition of existing ceramic fillers is solved, and the low density, high closed-cell rate and high thermal insulation performance of silicon foam is achieved, ensuring the stability and flame retardant properties of the material under flame conditions.

CN116574378BActive Publication Date: 2025-03-14HANGZHOU NORMAL UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310569345.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2022-06-28
Filing Date
2023-05-19
Publication Date
2025-03-14
Estimated Expiration
2043-05-19

AI Technical Summary

Technical Problem

The amount of existing ceramic filler added is too high, resulting in poor processing performance, high cell openness and high foam density, making it difficult to meet the demand for low-density of materials in extreme environments.

Method used

By controlling the controllable assembly of fillers, silanization modification and mixing process, the uniformity of the glue after mixing is improved, the foaming rate and closed cell ratio of silicon foam are increased, the foam density is reduced, and the efficiency of silicon foam porcelain formation is improved. Specific methods include using ceramicable filler, high melting point glass powder and hydroxy modified hexagonal boron nitride to carry out a hydrogen silicon addition condensation reaction, and controlling the filling to be assembled in situ into the outer surface of the foam and the internal structural framework.

Benefits of technology

The high-efficiency ceramic filling is achieved, the foam density is reduced, the closed cell rate and thermal insulation performance of the bubble cells are improved, and the stability and flame retardant properties of the material during flame attack are ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FHA0000009046410000011
    Figure FHA0000009046410000011
  • Figure FHA0000009046410000012
    Figure FHA0000009046410000012
  • Figure FHA0000009046410000021
    Figure FHA0000009046410000021
Patent Text Reader

Abstract

The present invention discloses an ablation-resistant, high-efficiency, heat-insulating, room-temperature-vulcanized silicone rubber foam and a preparation method thereof. The present invention first places hydroxyl-terminated polydimethylsiloxane, vinyl-terminated polydimethylsiloxane, a catalyst, an inhibitor, a ceramic emulsion foaming agent, a functionalized ceramic filler, and a heat-resistant additive in a planetary stirring kettle, and obtains a base rubber A after stirring; then, hydroxyl-terminated polydimethylsiloxane, vinyl-terminated polydimethylsiloxane, hydrogen-containing silicone oil, functionalized low-melting-point glass powder, and functionalized hexagonal boron nitride are placed in a planetary stirring kettle, and obtain a base rubber B after stirring; finally, the base rubber B is transferred to the base rubber A, and after vulcanization, it is placed in an oven for two-stage vulcanization to obtain the final product. The present invention has a low filler addition amount, a high foam closed cell rate, a low apparent density, an excellent heat insulation effect, and a stable internal structure of the foam. The method of the present invention is simple and efficient.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of organic silicon materials, and in particular relates to an ablation-resistant, highly efficient, heat-insulating, room-temperature vulcanized silicone rubber foam and a preparation method thereof. Background Art

[0002] Ceramic silicone rubber foam has attracted great attention due to its high thermal stability, excellent fire resistance, high elasticity and electrical insulation properties. It has been widely used in certain fields, such as aerospace, electronics, nuclear industry and power transmission. Ordinary flame retardant polymer materials will form ashes or droplets after flame ablation, and cannot play a long-term fire protection role. Ceramic silicone rubber foam can form strong and stable ceramics after encountering flame or high temperature attack. At the same time, the porous structure can block the transfer of heat, thereby protecting the internal devices from damage. There are three elements of heat transfer: heat conduction, heat convection, and heat radiation. The density and porous structure of silicone rubber foam are two important factors affecting the thermal insulation performance of foam materials. The thermal conductivity of pure silicone rubber is 0.27W / (m · K), while the thermal conductivity of air is much lower than that of silicone rubber (0.024W / (m · K), so low-density silicone rubber foam has better thermal insulation performance. In addition, the closed-cell structure of the foam can block the heat convection caused by the air temperature difference, further improving the thermal insulation efficiency. Therefore, while ensuring the high-efficiency flame retardancy and ceramicization of silicone rubber foam, reducing the density and increasing the closed-cell ratio are important research directions for the development of ablation-resistant and high-efficiency thermal insulation room temperature vulcanized silicone rubber foam materials.

[0003] The invention patent with patent number 201710799579.6 discloses a room temperature vulcanized ceramic silicone rubber foam sealant and its preparation method. Its components include α, ω-dihydroxy polydimethylsiloxane, precipitated silica, mica powder, ceramic additives, surface treatment agents, vinyl silicone oil, hydrogen-containing silicone oil, catalysts and foaming agents. Among them, the ceramic additive is one or more of aluminum silicate, magnesium silicate, boric acid, zinc borate, glass powder, and TiO2. The prepared ceramic silicone rubber foam sealant not only has the excellent properties of silicone foam sealant, but also forms a dense ceramic body under combustion or high temperature conditions, and has the characteristics of stable structure, stable fire resistance and good insulation performance. However, the filler content used in the preparation of the foaming material is high, the ceramicization efficiency is low, the viscosity of the rubber is large, the processing performance is poor, and the catalyst is seriously poisoned, resulting in poor mechanical properties of the foam material and a large apparent density (0.48~0.6g / cm 3 ), which is not conducive to blocking the transfer of heat and is difficult to meet the demand for low-density materials in extreme environments. Summary of the invention

[0004] One object of the present invention is to provide a room temperature vulcanized silicone rubber foam that is resistant to ablation and highly effective in insulating properties, in view of the problems in the prior art such as excessive addition of ceramic fillers, poor processing performance, high cell opening rate, and high density of foam materials.

[0005] The present invention improves the uniformity of the rubber after mixing by regulating and controlling the controllable assembly of fillers, silanization modification and mixing process, improves the foaming ratio and closed-cell rate of silicon foam, reduces the foam density and improves the ceramic efficiency of silicon foam. The filler is prepared into a W / O type ceramic emulsion foaming agent by using the abundant hydroxyl groups on the surface of ceramic fillers, high melting point glass powder and hydroxyl modified hexagonal boron nitride, and the ceramic fillers, high melting point glass powder and hydroxyl hexagonal boron nitride are controlled to be assembled in situ to the outer surface of the foam by using the silicon hydrogen addition condensation reaction, and the emulsion particles provide more nucleation sites for the foaming reaction, thereby reducing the foam density and improving the closed-cell rate of the foam. The ceramic fillers, low melting point glass powder and hydroxyl modified hexagonal boron nitride are silanized to improve the dispersibility of the fillers in the silicon foam matrix and reduce agglomeration, and the fillers are controlled to be assembled into the structural skeleton by using the silicon hydrogen addition reaction to give full play to the function of the ceramic fillers, improve the efficiency of the fillers, and reduce the density of the silicon foam. When the silicone foam surface is attacked by flames, the ceramic fillers and high-melting-point glass powder assembled on the foam surface can quickly undergo a ceramicization reaction to form a dense ceramic structure, which slows down the transfer of heat to the internal structure. The internal structure uses ceramic fillers and low-melting-point glass powder to slowly undergo a ceramicization reaction and form a dense and continuous ceramic structure with the surface, isolating it from flames and oxygen and preventing the silicone rubber foam from burning.

[0006] The vulcanized silicone rubber foam of the present invention comprises the following components blended and foamed, in parts by weight:

[0007]

[0008] Furthermore, the viscosity of the hydroxyl-terminated polydimethylsiloxane is 5000 to 20000 mPa. · s; the viscosity of the vinyl-terminated polydimethylsiloxane is 20000 to 50000 mPa · s; the hydrogen content of the hydrogen-containing silicone oil is 0.5-1.6%.

[0009] Further, the catalyst is a Castaplatin catalyst, whose chemical formula is C 24 H 54 O3PtSi6, concentration is 2000~5000ppm.

[0010] The inhibitor is a silicene compound with the structural formula: Among them, R 1 , R 2 and R 3are H, methyl or ethyl respectively, and R is cyclohexyl or isopropyl.

[0011] Furthermore, the ceramicizable emulsion foaming agent is a mixture of the following substances, measured in parts by weight:

[0012]

[0013] The emulsifier is one or more of Span 20, Span 60 and Span 80;

[0014] The viscosity of the hydroxyl-terminated polydimethylsiloxane is 1500-50000 mPa · s;

[0015] The melting point of the high melting point glass powder is 650-900°C;

[0016] The ceramic filler is one or more of montmorillonite, kaolin, wollastonite and halloysite;

[0017] The hydroxyl-modified hexagonal boron nitride is obtained by treating hexagonal boron nitride at high temperature for 0.5 to 2.0 hours, cooling it, and washing it with deionized water. The high temperature is 900 to 1200°C.

[0018] The emulsifier is mixed with hydroxyl-terminated polydimethylsiloxane, heated in a water bath to dissolve and mix evenly, and then high melting point glass powder, ceramic filler and hydroxyl-modified hexagonal boron nitride are added and mixed evenly to obtain a ceramic emulsion foaming agent. During the foaming process, the hydroxyl groups on the surface of the filler in the ceramic emulsion foaming agent react with the hydrogen-containing silicone oil to provide more foaming nucleation sites, thereby regulating the self-assembly of the ceramic filler to the surface of the pores.

[0019] Furthermore, the functionalized ceramic filler is obtained by grafting a ceramic filler with a silane coupling agent, and the ceramic filler is one or more of montmorillonite, kaolin, wollastonite, and halloysite.

[0020] The functionalized low-melting-point glass powder is obtained by grafting low-melting-point glass powder with a silane coupling agent, and the melting point of the low-melting-point glass powder is 350-600°C.

[0021] The functionalized hexagonal boron nitride is obtained by grafting hydroxyl-modified hexagonal boron nitride with a silane coupling agent, and the hydroxyl-modified hexagonal boron nitride is obtained by treating the hexagonal boron nitride at high temperature for 0.5 to 2.0 hours, cooling it, and washing it with deionized water. The high temperature is 900 to 1200°C. There are two purposes for adding hexagonal boron nitride: first, under the attack of ordinary flame (temperature below 1750°C), the silicon foam gradually forms a ceramic structure, and the hexagonal boron nitride has a lamellar structure to enhance the strength of the ceramic body; second, when the silicon foam is subjected to ultra-high temperature (greater than 1750°C) flame ablation, the silicon foam decomposes to form silicon dioxide and the ceramic filler melts to form a protective liquid film, and the high melting point boron nitride filler can increase the viscosity of the molten silicon dioxide system, effectively resist flame erosion, and improve the stability of the foam skeleton structure.

[0022] Add silane coupling agent to 70-80% ethanol aqueous solution, control the temperature at 60-80°C, adjust the pH to 3-5 with glacial acetic acid, and fully hydrolyze the silane coupling agent; then add ceramic filler, low melting point glass powder or hydroxyl modified hexagonal boron nitride, treat for 2-6 hours, adjust the pH to 9-10 with ammonia water, wash and dry with ethanol, and then obtain functionalized ceramic filler, functionalized low melting point glass powder or functionalized hexagonal boron nitride. The amount of silane coupling agent is 1-5% of the mass of ceramic filler, low melting point glass powder or hydroxyl modified hexagonal boron nitride.

[0023] The silane coupling agent is vinyl triethoxy silane, vinyl trimethoxy silane or vinyl tri (β-methoxyethoxy) silane.

[0024] Furthermore, the heat-resistant additive is one or more of SnO2, Fe2O3, CeO2, and Al2O3.

[0025] The present invention improves the ceramic forming efficiency of ceramic fillers, realizes efficient ceramicization and flame retardancy of silicon foam with less fillers added, and simultaneously utilizes the properties of the raw materials themselves to improve the rubber processing technology, improves the matching of the rubber vulcanization / foaming process during material foaming and molding, reduces the density of silicon foam, and further improves the closed cell rate of the foam material.

[0026] Another object of the present invention is to provide a method for preparing the ablation-resistant, high-efficiency, heat-insulating, room-temperature vulcanized silicone rubber foam. Specifically:

[0027] Step (1) Weigh 50 parts by weight of hydroxyl-terminated polydimethylsiloxane, 10 to 30 parts by weight of vinyl-terminated polydimethylsiloxane, 0.4 to 1.5 parts by weight of a catalyst, 0.1 to 0.5 parts by weight of an inhibitor, 5 to 10 parts by weight of a ceramic emulsion foaming agent, 3 to 15 parts by weight of a functionalized ceramic filler, and 1 to 3 parts by weight of a heat-resistant additive, place the mixture in a planetary stirring kettle, start a cold circulation system, control the temperature of the rubber material to be 15 to 25° C., and stir at a speed of 1000 to 2000 rad / min for 20 to 30 minutes to obtain a base rubber A;

[0028] Step (2) Weigh 50 parts by weight of hydroxyl-terminated polydimethylsiloxane, 10 to 30 parts by weight of vinyl-terminated polydimethylsiloxane, 20 to 40 parts by weight of hydrogen-containing silicone oil, 3 to 15 parts by weight of functionalized low-melting-point glass powder, and 1 to 5 parts by weight of functionalized hexagonal boron nitride, place them in a planetary stirring kettle, start a cold circulation system, control the temperature of the rubber material to 15 to 25° C., and stir at a speed of 1000 to 2000 rad / min for 20 to 30 min to obtain a base rubber B;

[0029] Step (3) transfers the base rubber B to the base rubber A, starts the cold circulation system, stirs at a speed of 4000-6000 rad / min for 1-2 min, transfers to the mold, vulcanizes at room temperature for 10-20 min, puts into an oven, and vulcanizes at 60-80°C for 1-2 h to obtain ablation-resistant, high-efficiency, heat-insulating room temperature vulcanized silicone rubber foam. High-speed stirring introduces more air micronuclei, provides more bubble nucleation sites, reduces foam density, and can also increase closed cell rate. In addition, by adding the hydrogen-containing silicone oil component to the catalyst component and utilizing the density difference to allow the hydrogen-containing silicone oil component to settle naturally, the mixing efficiency can also be improved.

[0030] The present invention involves in-situ assembly of fillers and matching of specific mixing processes. Functional fillers are efficiently assembled on the foam surface and internal structural skeleton, solving the problem that silicone rubber foam needs to add high-content fillers to achieve ceramicization and flame retardancy, and reduces foam density, improves the closed cell rate, uniformity and foam thermal insulation performance. Compared with the prior art, the present invention has the following beneficial effects:

[0031] (1) The material of the present invention is self-assembled in situ by fillers during the foaming process. When encountering flame attack, the foam surface and the inside of the skeleton jointly form dense ceramics under a temperature gradient. Silicon foam ceramics can be achieved by adding less functional fillers, and the flame retardant performance is good. The ceramic structure formed when encountering flame attack is stable / dense and has high strength. This low content of fillers can also ensure low viscosity of the rubber and good processing performance.

[0032] (2) The method of the present invention optimizes the process, has high mixing efficiency, uniform pores, high closed cell rate, low foam density, and good thermal insulation performance. DETAILED DESCRIPTION

[0033] The present invention will be further described below in conjunction with specific examples, and all fractions in the following examples and comparative examples are weight parts. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The operating methods in the following examples where specific conditions are not specified are usually based on conventional conditions or the conditions recommended by the manufacturer.

[0034] Example 1.

[0035] Montmorillonite is grafted with vinyl triethoxysilane coupling agent to obtain functionalized ceramic filler: 0.15 parts of vinyl triethoxysilane coupling agent are added to 70% ethanol aqueous solution, the temperature is controlled at 80°C, the pH is adjusted to 4 with glacial acetic acid, and the silane coupling agent is fully hydrolyzed; then 3 parts of montmorillonite are added, and after treating for 6 hours, the pH is adjusted to 9.5 with ammonia water, and the solution is washed with ethanol and dried to obtain functionalized ceramic filler.

[0036] Glass powder with a melting point of 500°C is grafted with vinyl triethoxysilane coupling agent to obtain functionalized low-melting-point glass powder: 0.15 parts of vinyl triethoxysilane coupling agent are added to 70% ethanol aqueous solution, the temperature is controlled at 80°C, and the pH is adjusted to 4 with glacial acetic acid to fully hydrolyze the silane coupling agent; then 3 parts of glass powder are added, and after treating for 6 hours, the pH is adjusted to 9.5 with ammonia water, and the solution is washed and dried with ethanol to obtain functionalized low-melting-point glass powder.

[0037] The hexagonal boron nitride was treated at 1000° C. for 1 hour, cooled and washed with deionized water to obtain hydroxyl-modified hexagonal boron nitride.

[0038] Functionalized hexagonal boron nitride is obtained by grafting hydroxyl-modified hexagonal boron nitride with vinyl triethoxysilane coupling agent: 0.05 parts of vinyl triethoxysilane coupling agent are added to 70% ethanol aqueous solution, the temperature is controlled at 80°C, and the pH is adjusted to 4 with glacial acetic acid to fully hydrolyze the silane coupling agent; then 1 part of hydroxyl-modified hexagonal boron nitride is added, and after treating for 6 hours, the pH is adjusted to 9.5 with ammonia water, and the solution is washed with ethanol and dried to obtain functionalized hexagonal boron nitride.

[0039] Mix 5 parts of Span 20 with 100 parts of a 20000 mPa · s hydroxyl-terminated polydimethylsiloxane is mixed, heated in a water bath to dissolve and mix evenly, then 40 parts of glass powder with a melting point of 900°C, 30 parts of montmorillonite and 10 parts of the prepared hydroxyl-modified hexagonal boron nitride are added and continued to mix evenly to obtain a ceramic emulsion foaming agent.

[0040] Prepare ablation-resistant, high-efficiency, thermal-insulating room temperature vulcanized silicone rubber foam as follows:

[0041] Step (1) 50 parts of a 10000 mPa · s of hydroxyl-terminated polydimethylsiloxane, 10 parts of viscosity 20000mPa · s vinyl-terminated polydimethylsiloxane, 1.5 parts of 2000 ppm Castaplatin catalyst C 24 H 54 O3PtSi6, 0.2 parts of inhibitor, 5 parts of ceramic emulsion foaming agent, 3 parts of functional ceramic filler, and 1 part of heat-resistant additive SnO2 were placed in a planetary stirring kettle, the cold circulation system was turned on, the rubber temperature was controlled to 15°C, and the speed was 1000 rad / min for 30 minutes to obtain base rubber A. The inhibitor is a silane compound with the structural formula: Among them, R 1 , R 2 , R 3 is H, and R is cyclohexyl.

[0042] Step (2) 50 parts of a 10000 mPa · s of hydroxyl-terminated polydimethylsiloxane, 10 parts of viscosity 20000mPa · s of vinyl-terminated polydimethylsiloxane, 40 parts of hydrogen-containing silicone oil with a hydrogen content of 0.5%, 3 parts of functionalized low-melting-point glass powder, and 1 part of functionalized hexagonal boron nitride were placed in a planetary stirring kettle, the cold circulation system was turned on, the rubber temperature was controlled at 15°C, and the rubber was stirred at a speed of 1000 rad / min for 30 minutes to obtain base rubber B.

[0043] Step (3) transfer the base rubber B to the base rubber A, start the cold circulation system, stir at a speed of 4000 rad / min for 2 minutes, transfer to the mold, vulcanize at room temperature for 15 minutes, put into an oven, and vulcanize at 60°C for 2 hours to obtain ablation-resistant, high-efficiency, heat-insulating room temperature vulcanized silicone rubber foam.

[0044] Example 2.

[0045] Kaolin is grafted with vinyl trimethoxy silane coupling agent to obtain functionalized ceramic filler: 0.1 parts of vinyl trimethoxy silane coupling agent are added to 75% ethanol aqueous solution, the temperature is controlled at 75°C, the pH is adjusted to 3 with glacial acetic acid, and the silane coupling agent is fully hydrolyzed; then 4 parts of kaolin are added, and after treating for 5 hours, the pH is adjusted to 9.0 with ammonia water, and the solution is washed with ethanol and dried to obtain functionalized ceramic filler.

[0046] Glass powder with a melting point of 400°C is grafted with a vinyl trimethoxysilane coupling agent to obtain a functionalized low-melting-point glass powder: 0.1 parts of vinyl trimethoxysilane coupling agent are added to a 75% ethanol aqueous solution, the temperature is controlled at 75°C, the pH is adjusted to 3 with glacial acetic acid, and the silane coupling agent is fully hydrolyzed; then 4 parts of glass powder are added, and after treating for 5 hours, the pH is adjusted to 9.0 with ammonia water, and the solution is washed with ethanol and dried to obtain a functionalized low-melting-point glass powder.

[0047] The hexagonal boron nitride was treated at 900° C. for 2 hours, cooled and washed with deionized water to obtain hydroxyl-modified hexagonal boron nitride.

[0048] Functionalized hexagonal boron nitride is obtained by grafting hydroxyl-modified hexagonal boron nitride with vinyl trimethoxy silane coupling agent: 0.06 parts of vinyl trimethoxy silane coupling agent are added to 75% ethanol aqueous solution, the temperature is controlled at 75°C, the pH is adjusted to 3 with glacial acetic acid, and the silane coupling agent is fully hydrolyzed; then 1.5 parts of hydroxyl-modified hexagonal boron nitride are added, and after treating for 5 hours, the pH is adjusted to 9.0 with ammonia water, and the solution is washed with ethanol and dried to obtain functionalized hexagonal boron nitride.

[0049] Mix 8 parts of Span 60 with 100 parts of a 1500 mPa · s hydroxyl-terminated polydimethylsiloxane is mixed, heated in a water bath to dissolve and mix evenly, then 30 parts of glass powder with a melting point of 750°C, 30 parts of montmorillonite, 40 parts of kaolin and 15 parts of the prepared hydroxyl-modified hexagonal boron nitride are added and mixed evenly to obtain a ceramic emulsion foaming agent.

[0050] Prepare ablation-resistant, high-efficiency, thermal-insulating room temperature vulcanized silicone rubber foam as follows:

[0051] Step (1) 50 parts of a 5000 mPa · s of hydroxyl-terminated polydimethylsiloxane, 30 parts of viscosity 30000mPa · s vinyl-terminated polydimethylsiloxane, 1.2 parts of 2500 ppm Castaplatin catalyst C 24 H 54 O3PtSi6, 0.1 part of inhibitor, 6 parts of ceramic emulsion foaming agent, 4 parts of functional ceramic filler, and 1.2 parts of heat-resistant additive Fe2O3 were placed in a planetary stirring kettle, the cold circulation system was turned on, the rubber temperature was controlled to 16°C, and the speed was 1200 rad / min for 25 minutes to obtain base rubber A. The inhibitor is a silane compound with the structural formula: Among them, R 1 , R 2 , R 3 R is methyl and R is isopropyl.

[0052] Step (2) 50 parts of a 5000 mPa · s of hydroxyl-terminated polydimethylsiloxane, 30 parts of viscosity 30000mPa · s of vinyl-terminated polydimethylsiloxane, 36 parts of hydrogen-containing silicone oil with a hydrogen content of 0.6%, 4 parts of functionalized low-melting-point glass powder, and 1.5 parts of functionalized hexagonal boron nitride were placed in a planetary stirring kettle, the cold circulation system was turned on, the rubber temperature was controlled at 18°C, and the mixture was stirred at a speed of 1200 rad / min for 28 minutes to obtain base rubber B.

[0053] Step (3) transfer the base rubber B to the base rubber A, start the cold circulation system, stir at a speed of 4200 rad / min for 100 s, transfer to the mold, vulcanize at room temperature for 10 min, put into an oven, and vulcanize at 70°C for 2 h to obtain ablation-resistant, high-efficiency, heat-insulating room temperature vulcanized silicone rubber foam.

[0054] Example 3.

[0055] Vinyl tri(β-methoxyethoxy)silane coupling agent is used to graft wollastonite to obtain a functionalized ceramic filler: 0.1 parts of vinyl tri(β-methoxyethoxy)silane coupling agent is added to an 80% ethanol aqueous solution, the temperature is controlled at 70°C, the pH is adjusted to 5 with glacial acetic acid, and the silane coupling agent is fully hydrolyzed; then 5 parts of wollastonite are added, and after treating for 2 hours, the pH is adjusted to 9.8 with ammonia water, and the solution is washed with ethanol and dried to obtain a functionalized ceramic filler.

[0056] Glass powder with a melting point of 450°C is grafted with a vinyl trimethoxysilane coupling agent to obtain a functionalized low-melting-point glass powder: 0.1 parts of vinyl trimethoxysilane coupling agent are added to an 80% ethanol aqueous solution, the temperature is controlled at 70°C, the pH is adjusted to 5 with glacial acetic acid, and the silane coupling agent is fully hydrolyzed; then 5 parts of glass powder are added, and after treating for 2 hours, the pH is adjusted to 9.8 with ammonia water, and the solution is washed and dried with ethanol to obtain a functionalized low-melting-point glass powder.

[0057] The hexagonal boron nitride was treated at 1200° C. for 0.5 hours, cooled and washed with deionized water to obtain hydroxyl-modified hexagonal boron nitride.

[0058] Functionalized hexagonal boron nitride is obtained by grafting hydroxyl-modified hexagonal boron nitride with vinyl triethoxysilane coupling agent: 0.06 parts of vinyl triethoxysilane coupling agent are added to 80% ethanol aqueous solution, the temperature is controlled at 70°C, and the pH is adjusted to 5 with glacial acetic acid to fully hydrolyze the silane coupling agent; then 2 parts of hydroxyl-modified hexagonal boron nitride are added, and after treating for 2 hours, the pH is adjusted to 9.8 with ammonia water, and the solution is washed with ethanol and dried to obtain functionalized hexagonal boron nitride.

[0059] Mix 10 parts of Span 80 with 100 parts of a 5000 mPa ·s hydroxyl-terminated polydimethylsiloxane is mixed, heated in a water bath to dissolve and mix evenly, and then 70 parts of glass powder with a melting point of 700°C, 10 parts of kaolin and 20 parts of the prepared hydroxyl-modified hexagonal boron nitride are added and continued to mix evenly to obtain a ceramic emulsion foaming agent.

[0060] Prepare ablation-resistant, high-efficiency, thermal-insulating room temperature vulcanized silicone rubber foam as follows:

[0061] Step (1) 50 parts of a 20000 mPa · s of hydroxyl-terminated polydimethylsiloxane, 12 parts of viscosity 40000mPa · s vinyl-terminated polydimethylsiloxane, 1 part of 3000 ppm Castaplatin catalyst C 24 H 54 O3PtSi6, 0.3 parts of inhibitor, 7 parts of ceramic emulsion foaming agent, 5 parts of functional ceramic filler, and 1.5 parts of heat-resistant additive CeO2 were placed in a planetary stirring kettle, the cold circulation system was turned on, the rubber temperature was controlled to 18°C, and the speed was 1500 rad / min for 22 minutes to obtain base rubber A. The inhibitor is a silane compound with the structural formula: Among them, R 1 , R 2 , R 3 R is ethyl and R is cyclohexyl.

[0062] Step (2) 50 parts of a 20000 mPa · s of hydroxyl-terminated polydimethylsiloxane, 12 parts of viscosity 40000mPa · s of vinyl-terminated polydimethylsiloxane, 32 parts of hydrogen-containing silicone oil with a hydrogen content of 0.8%, 5 parts of functionalized low-melting-point glass powder, and 2 parts of functionalized hexagonal boron nitride were placed in a planetary stirring kettle, the cold circulation system was turned on, the rubber temperature was controlled at 20°C, and the mixture was stirred at a speed of 1300 rad / min for 26 minutes to obtain base rubber B.

[0063] Step (3) transfer the base rubber B to the base rubber A, start the cold circulation system, stir at a speed of 4500 rad / min for 80 seconds, transfer to the mold, vulcanize at room temperature for 12 minutes, put into an oven, and vulcanize in the second stage at 70°C for 1 hour and 45 minutes to obtain ablation-resistant, high-efficiency, heat-insulating room temperature vulcanized silicone rubber foam.

[0064] Example 4.

[0065] Vinyltrimethoxysilane coupling agent is used to graft montmorillonite and kaolin in a weight ratio of 2:3 to obtain a functionalized ceramic filler: 0.2 parts of vinyltrimethoxysilane coupling agent is added to a 72% ethanol aqueous solution, the temperature is controlled at 78°C, and the pH is adjusted to 3.5 with glacial acetic acid to fully hydrolyze the silane coupling agent; then 2.4 parts of montmorillonite and 3.6 parts of kaolin are added, and after treating for 3 hours, the pH is adjusted to 10.0 with ammonia water, and the solution is washed with ethanol and dried to obtain a functionalized ceramic filler.

[0066] Glass powder with a melting point of 600°C is grafted with vinyl trimethoxysilane coupling agent to obtain functionalized low-melting-point glass powder: 0.2 parts of vinyl trimethoxysilane coupling agent are added to 72% ethanol aqueous solution, the temperature is controlled at 78°C, the pH is adjusted to 3.5 with glacial acetic acid, and the silane coupling agent is fully hydrolyzed; then 6 parts of glass powder are added, and after treating for 3 hours, the pH is adjusted to 10.0 with ammonia water, and the solution is washed and dried with ethanol to obtain functionalized ceramic filler.

[0067] The hexagonal boron nitride was treated at 1100° C. for 50 minutes, cooled and washed with deionized water to obtain hydroxyl-modified hexagonal boron nitride.

[0068] Functionalized hexagonal boron nitride is obtained by grafting hydroxyl-modified hexagonal boron nitride with vinyl tri(β-methoxyethoxy) silane coupling agent: 0.05 parts of vinyl tri(β-methoxyethoxy) silane coupling agent is added to 72% ethanol aqueous solution, the temperature is controlled at 78°C, the pH is adjusted to 3.5 with glacial acetic acid, and the silane coupling agent is fully hydrolyzed; then 2.5 parts of hydroxyl-modified hexagonal boron nitride are added, and after treating for 3 hours, the pH is adjusted to 10.0 with ammonia water, and the solution is washed with ethanol and dried to obtain functionalized hexagonal boron nitride.

[0069] Mix 6 parts of Span 20, 6 parts of Span 60 and 100 parts of a 10000 mPa · s hydroxyl-terminated polydimethylsiloxane is mixed, heated in a water bath to dissolve and mix evenly, and then 50 parts of glass powder with a melting point of 650°C, 50 parts of wollastonite and 18 parts of the prepared hydroxyl-modified hexagonal boron nitride are added and continued to be mixed evenly to obtain a ceramic emulsion foaming agent.

[0070] Prepare ablation-resistant, high-efficiency, thermal-insulating room temperature vulcanized silicone rubber foam as follows:

[0071] Step (1) 50 parts of a 15000 mPa · s of hydroxyl-terminated polydimethylsiloxane, 15 parts of viscosity 50000mPa · s vinyl-terminated polydimethylsiloxane, 0.8 parts of 3500 ppm Castaplatin catalyst C 24 H 54O3PtSi6, 0.4 parts of inhibitor, 8 parts of ceramic emulsion foaming agent, 6 parts of functional ceramic filler, and 3 parts of heat-resistant additive Al2O3 were placed in a planetary stirring kettle, the cold circulation system was turned on, the rubber temperature was controlled to 20°C, and the speed was 1600 rad / min for 20 minutes to obtain base rubber A. The inhibitor is a silane compound with the structural formula: Among them, R 1 , R 2 , R 3 is H, and R is isopropyl.

[0072] Step (2) 50 parts of a 10000 mPa · s of hydroxyl-terminated polydimethylsiloxane, 10 parts of viscosity 20000mPa · s of vinyl-terminated polydimethylsiloxane, 30 parts of hydrogen-containing silicone oil with a hydrogen content of 1%, 6 parts of functionalized low-melting-point glass powder, and 2.5 parts of functionalized hexagonal boron nitride were placed in a planetary stirring kettle, the cold circulation system was turned on, the rubber temperature was controlled at 22°C, and stirred at a speed of 1500 rad / min for 24 minutes to obtain base rubber B.

[0073] Step (3) transfer the base rubber B to the base rubber A, start the cold circulation system, stir at a speed of 5000 rad / min for 70 seconds, transfer to the mold, vulcanize at room temperature for 16 minutes, put into an oven, and vulcanize in the second stage at 65°C for 1 hour and 50 minutes to obtain ablation-resistant, high-efficiency, heat-insulating room temperature vulcanized silicone rubber foam.

[0074] Example 5.

[0075] Halloysite is grafted with vinyl triethoxysilane coupling agent to obtain functionalized ceramic filler: 0.1 parts of vinyl triethoxysilane coupling agent are added to 78% ethanol aqueous solution, the temperature is controlled at 72°C, the pH is adjusted to 4.5 with glacial acetic acid, and the silane coupling agent is fully hydrolyzed; then 8 parts of montmorillonite are added, and after treating for 4 hours, the pH is adjusted to 9.2 with ammonia water, and the solution is washed with ethanol and dried to obtain functionalized ceramic filler.

[0076] Glass powder with a melting point of 580°C is grafted with a vinyl trimethoxysilane coupling agent to obtain a functionalized low-melting-point glass powder: 0.1 parts of vinyl trimethoxysilane coupling agent are added to a 78% ethanol aqueous solution, the temperature is controlled at 72°C, the pH is adjusted to 4.5 with glacial acetic acid, and the silane coupling agent is fully hydrolyzed; then 8 parts of glass powder are added, and after treating for 4 hours, the pH is adjusted to 9.2 with ammonia water, and the solution is washed and dried with ethanol to obtain a functionalized low-melting-point glass powder.

[0077] The hexagonal boron nitride was treated at 1150° C. for 45 minutes, cooled and then washed with deionized water to obtain hydroxyl-modified hexagonal boron nitride.

[0078] Functionalized hexagonal boron nitride is obtained by grafting hydroxyl-modified hexagonal boron nitride with vinyl trimethoxy silane coupling agent: 0.03 parts of vinyl trimethoxy silane coupling agent is added to 78% ethanol aqueous solution, the temperature is controlled at 72°C, the pH is adjusted to 4.5 with glacial acetic acid, and the silane coupling agent is fully hydrolyzed; then 3 parts of hydroxyl-modified hexagonal boron nitride are added, and after treating for 4 hours, the pH is adjusted to 9.2 with ammonia water, and the solution is washed with ethanol and dried to obtain functionalized hexagonal boron nitride.

[0079] Mix 5 parts of Span 20, 5 parts of Span 60, 5 parts of Span 80 and 100 parts of a viscosity of 50000 mPa. · s hydroxyl-terminated polydimethylsiloxane is mixed, heated in a water bath to dissolve and mix evenly, and then 40 parts of glass powder with a melting point of 800°C, 60 parts of halloysite and 12 parts of hydroxyl-modified hexagonal boron nitride are added and mixed evenly to obtain a ceramic emulsion foaming agent.

[0080] Prepare ablation-resistant, high-efficiency, thermal-insulating room temperature vulcanized silicone rubber foam as follows:

[0081] Step (1) 50 parts of a 18000 mPa · s of hydroxyl-terminated polydimethylsiloxane, 18 parts of viscosity 25000mPa · s vinyl-terminated polydimethylsiloxane, 0.6 parts of 4000 ppm Castaplatin catalyst C 24 H 54 O3PtSi6, 0.5 parts of inhibitor, 9 parts of ceramic emulsion foaming agent, 8 parts of functionalized ceramic filler, 1 part of heat-resistant additive SnO2 and 1 part of heat-resistant additive Fe2O3 were placed in a planetary stirring kettle, the cold circulation system was turned on, the rubber temperature was controlled to 22°C, and the speed was 1800 rad / min for 24 minutes to obtain base rubber A. The inhibitor is a silane compound with the structural formula: Among them, R 1 and R 2 is methyl, R 3 R is ethyl and R is isopropyl.

[0082] Step (2) 50 parts of a viscosity of 8000 mPa · s of hydroxyl-terminated polydimethylsiloxane, 20 parts of viscosity 12000mPa · s of vinyl-terminated polydimethylsiloxane, 25 parts of hydrogen-containing silicone oil with a hydrogen content of 1.2%, 8 parts of functionalized low-melting-point glass powder, and 3 parts of functionalized hexagonal boron nitride were placed in a planetary stirring kettle, the cold circulation system was turned on, the rubber temperature was controlled at 24°C, and stirred at a speed of 1600 rad / min for 22 minutes to obtain base rubber B.

[0083] Step (3) transfer the base rubber B to the base rubber A, start the cold circulation system, stir at a speed of 5400 rad / min for 2 minutes, transfer to the mold, vulcanize at room temperature for 18 minutes, put into an oven, and vulcanize at 80°C for 1 hour and 15 minutes to obtain ablation-resistant, high-efficiency, heat-insulating room temperature vulcanized silicone rubber foam.

[0084] Example 6.

[0085] Vinyl tri(β-methoxyethoxy) silane coupling agent is used to graft wollastonite and halloysite in a weight ratio of 3:1 to obtain a functionalized ceramic filler: 0.1 parts of vinyl tri(β-methoxyethoxy) silane coupling agent is added to a 75% ethanol aqueous solution, the temperature is controlled at 72°C, the pH is adjusted to 4.2 with glacial acetic acid, and the silane coupling agent is fully hydrolyzed; then 7.5 parts of wollastonite and 2.5 parts of halloysite are added, and after treating for 4.5 hours, the pH is adjusted to 9.6 with aqueous ammonia, and the mixture is washed with ethanol and dried to obtain a functionalized ceramic filler.

[0086] Glass powder with a melting point of 550°C is grafted with vinyl tri(β-methoxyethoxy) silane coupling agent to obtain functionalized low-melting-point glass powder: 0.1 parts of vinyl tri(β-methoxyethoxy) silane coupling agent is added to a 75% ethanol aqueous solution, the temperature is controlled at 72°C, the pH is adjusted to 4.2 with glacial acetic acid, and the silane coupling agent is fully hydrolyzed; then 10 parts of glass powder are added, and after treating for 4.5 hours, the pH is adjusted to 9.6 with ammonia water, and the solution is washed with ethanol and dried to obtain functionalized low-melting-point glass powder.

[0087] The hexagonal boron nitride was treated at 1050° C. for 80 minutes, cooled and then washed with deionized water to obtain hydroxyl-modified hexagonal boron nitride.

[0088] Functionalized hexagonal boron nitride is obtained by grafting hydroxyl-modified hexagonal boron nitride with vinyl vinyl tri(β-methoxyethoxy) silane coupling agent: 0.1 parts of vinyl vinyl tri(β-methoxyethoxy) silane coupling agent is added to 75% ethanol aqueous solution, the temperature is controlled at 72°C, the pH is adjusted to 4.2 with glacial acetic acid, and the silane coupling agent is fully hydrolyzed; then 3.5 parts of hydroxyl-modified hexagonal boron nitride are added, and after treating for 4.5 hours, the pH is adjusted to 9.6 with ammonia water, and the solution is washed with ethanol and dried to obtain functionalized hexagonal boron nitride.

[0089] Mix 6 parts of Span 20 with 100 parts of a 30000 mPa · s hydroxyl-terminated polydimethylsiloxane is mixed, heated in a water bath to dissolve and mix evenly, then 20 parts of glass powder with a melting point of 850°C, 20 parts of wollastonite, 10 parts of halloysite and 10 parts of the prepared hydroxyl-modified hexagonal boron nitride are added and continued to mix evenly to obtain a ceramic emulsion foaming agent.

[0090] Prepare ablation-resistant, high-efficiency, thermal-insulating room temperature vulcanized silicone rubber foam as follows:

[0091] Step (1) 50 parts of a 8000 mPa · s of hydroxyl-terminated polydimethylsiloxane, 20 parts of viscosity 35000mPa · s vinyl-terminated polydimethylsiloxane, 0.5 parts of 4500ppm Castaplatin catalyst C 24 H 54 O3PtSi6, 0.4 parts of inhibitor, 10 parts of ceramic emulsion foaming agent, 10 parts of functionalized ceramic filler, and 2.5 parts of heat-resistant additive SnO2 were placed in a planetary stirring kettle, the cold circulation system was turned on, the rubber temperature was controlled to 24°C, and the mixture was stirred at a speed of 1000 rad / min for 30 minutes to obtain base rubber A. The inhibitor is a silane compound with the structural formula: Among them, R 1 For H, R 2 is methyl, R 3 R is ethyl and R is cyclohexyl.

[0092] Step (2) 50 parts of a 12000 mPa · s of hydroxyl-terminated polydimethylsiloxane, 30 parts of viscosity 40000mPa · s of vinyl-terminated polydimethylsiloxane, 24 parts of hydrogen-containing silicone oil with a hydrogen content of 1.3%, 10 parts of functionalized low-melting-point glass powder, and 3.5 parts of functionalized hexagonal boron nitride were placed in a planetary stirring kettle, the cold circulation system was turned on, the rubber temperature was controlled at 25°C, and stirred at a speed of 1800 rad / min for 21 minutes to obtain base rubber B.

[0093] Step (3) transfer the base rubber B to the base rubber A, start the cold circulation system, stir at a speed of 5500 rad / min for 1 min, transfer to the mold, vulcanize at room temperature for 20 min, put into an oven, and vulcanize in the second stage at 75°C for 1 h to obtain ablation-resistant, high-efficiency, heat-insulating room temperature vulcanized silicone rubber foam.

[0094] Example 7.

[0095] Vinyl triethoxysilane coupling agent is used to graft wollastonite to obtain functionalized ceramic filler: 0.2 parts of vinyl triethoxysilane coupling agent is added to 75% ethanol aqueous solution, the temperature is controlled at 75°C, and the pH is adjusted to 3.2 with glacial acetic acid to fully hydrolyze the silane coupling agent; then 12 parts of wollastonite is added, and after treating for 3.5 hours, the pH is adjusted to 9.1 with ammonia water, and the solution is washed with ethanol and dried to obtain functionalized ceramic filler.

[0096] Glass powder with a melting point of 350°C is grafted with a vinyl tri(β-methoxyethoxy) silane coupling agent to obtain a functionalized low-melting-point glass powder: 0.2 parts of vinyl tri(β-methoxyethoxy) silane coupling agent is added to a 75% ethanol aqueous solution, the temperature is controlled at 75°C, the pH is adjusted to 3.2 with glacial acetic acid, and the silane coupling agent is fully hydrolyzed; then 12 parts of glass powder are added, and after treating for 3.5 hours, the pH is adjusted to 9.1 with ammonia water, and the solution is washed with ethanol and dried to obtain a functionalized low-melting-point glass powder.

[0097] The hexagonal boron nitride was treated at 980° C. for 90 minutes, cooled and then washed with deionized water to obtain hydroxyl-modified hexagonal boron nitride.

[0098] Functionalized hexagonal boron nitride is obtained by grafting hydroxyl-modified hexagonal boron nitride with vinyl triethoxysilane coupling agent: 0.1 parts of vinyl triethoxysilane coupling agent are added to 75% ethanol aqueous solution, the temperature is controlled at 75°C, the pH is adjusted to 3.2 with glacial acetic acid, and the silane coupling agent is fully hydrolyzed; then 5 parts of hydroxyl-modified hexagonal boron nitride are added, and after treating for 3.5 hours, the pH is adjusted to 9.1 with ammonia water, and the solution is washed with ethanol and dried to obtain functionalized hexagonal boron nitride.

[0099] Mix 9 parts of Span 60 with 100 parts of a 3000 mPa · s hydroxyl-terminated polydimethylsiloxane is mixed, and after heating in a water bath to dissolve and mix evenly, 10 parts of glass powder with a melting point of 680°C, 15 parts of montmorillonite, 15 parts of kaolin, 15 parts of wollastonite, 15 parts of halloysite and 15 parts of the prepared hydroxyl-modified hexagonal boron nitride are added and continued to be mixed evenly to obtain a ceramic emulsion foaming agent.

[0100] Prepare ablation-resistant, high-efficiency, thermal-insulating room temperature vulcanized silicone rubber foam as follows:

[0101] Step (1) 50 parts of a 12000 mPa · s of hydroxyl-terminated polydimethylsiloxane, 25 parts of viscosity 45000mPa · s vinyl-terminated polydimethylsiloxane, 0.4 parts of 5000 ppm Castaplatin catalyst C 24 H 54 O3PtSi6, 0.3 parts of inhibitor, 6.5 parts of ceramic emulsion foaming agent, 12 parts of functionalized ceramic filler, 1 part of heat-resistant additive SnO2, 1 part of heat-resistant additive CeO2 and 1 part of heat-resistant additive Al2O3 were placed in a planetary stirring kettle, the cold circulation system was turned on, the rubber temperature was controlled to 25°C, and the rubber was stirred at a speed of 2000 rad / min for 20 minutes to obtain base rubber A. The inhibitor is a silane compound with the structural formula: Among them, R 1 and R 2 For H, R3 R is methyl and R is isopropyl.

[0102] Step (2) 50 parts of a 9000 mPa · s of hydroxyl-terminated polydimethylsiloxane, 16 parts of viscosity 25000mPa · s of vinyl-terminated polydimethylsiloxane, 20 parts of hydrogen-containing silicone oil with a hydrogen content of 1.6%, 12 parts of functionalized low-melting-point glass powder, and 5 parts of functionalized hexagonal boron nitride were placed in a planetary stirring kettle, the cold circulation system was turned on, the rubber temperature was controlled at 20°C, and the rubber was stirred at a speed of 2000 rad / min for 20 minutes to obtain base rubber B.

[0103] Step (3) transfer the base rubber B to the base rubber A, start the cold circulation system, stir at a speed of 6000 rad / min for 1 min, transfer to the mold, vulcanize at room temperature for 15 min, put into an oven, and vulcanize in the second stage at 78°C for 1 h to obtain ablation-resistant, high-efficiency, heat-insulating room temperature vulcanized silicone rubber foam.

[0104] Example 8.

[0105] Montmorillonite was grafted with vinyl trimethoxysilane coupling agent to obtain functionalized ceramic filler: 0.5 parts of vinyl trimethoxysilane coupling agent was added to 75% ethanol aqueous solution, the temperature was controlled at 75°C, the pH was adjusted to 3.4 with glacial acetic acid, and the silane coupling agent was fully hydrolyzed; then 15 parts of montmorillonite was added, and after treating for 2.5 hours, the pH was adjusted to 9.7 with ammonia water, and the solution was washed with ethanol and dried to obtain functionalized ceramic filler.

[0106] Glass powder with a melting point of 420°C is grafted with vinyl triethoxysilane coupling agent to obtain functionalized low-melting-point glass powder: 0.5 parts of vinyl triethoxysilane coupling agent is added to 75% ethanol aqueous solution, the temperature is controlled at 75°C, and the pH is adjusted to 3.4 with glacial acetic acid to fully hydrolyze the silane coupling agent; then 15 parts of glass powder are added, and after treating for 2.5 hours, the pH is adjusted to 9.7 with ammonia water, and the solution is washed with ethanol and dried to obtain functionalized low-melting-point glass powder.

[0107] The hexagonal boron nitride was treated at 950° C. for 100 minutes, cooled and washed with deionized water to obtain hydroxyl-modified hexagonal boron nitride.

[0108] Functionalized hexagonal boron nitride is obtained by grafting hydroxyl-modified hexagonal boron nitride with vinyl tri(β-methoxyethoxy) silane coupling agent: 0.1 parts of vinyl tri(β-methoxyethoxy) silane coupling agent is added to 75% ethanol aqueous solution, the temperature is controlled at 75°C, and the pH is adjusted to 3.4 with glacial acetic acid to fully hydrolyze the silane coupling agent; then 4.5 parts of hydroxyl-modified hexagonal boron nitride are added, and after treating for 2.5 hours, the pH is adjusted to 9.7 with ammonia water, and the solution is washed with ethanol and dried to obtain functionalized hexagonal boron nitride.

[0109] Mix 7 parts of Span 20, 7 parts of Span 60 and 100 parts of a 15000 mPa · s hydroxyl-terminated polydimethylsiloxane is mixed, heated in a water bath to dissolve and mix evenly, and then 50 parts of glass powder with a melting point of 780°C, 50 parts of kaolin and 18 parts of the prepared hydroxyl-modified hexagonal boron nitride are added and continued to mix evenly to obtain a ceramic emulsion foaming agent.

[0110] Prepare ablation-resistant, high-efficiency, thermal-insulating room temperature vulcanized silicone rubber foam as follows:

[0111] Step (1) 50 parts of a 6000 mPa · s of hydroxyl-terminated polydimethylsiloxane, 28 parts of viscosity 18000mPa · s vinyl-terminated polydimethylsiloxane, 1.1 parts of 3600 ppm Castaplatin catalyst C 24 H 54 O3PtSi6, 0.2 parts of inhibitor, 7.5 parts of ceramic emulsion foaming agent, 15 parts of functionalized ceramic filler, and 1.8 parts of heat-resistant additive SnO2 were placed in a planetary stirring kettle, the cold circulation system was turned on, the rubber temperature was controlled to 20°C, and the speed was 1300 rad / min for 25 minutes to obtain base rubber A. The inhibitor is a silane compound with the structural formula: Among them, R 1 and R 2 Ethyl, R 3 is H, and R is cyclohexyl.

[0112] Step (2) 50 parts of a 18000 mPa · s of hydroxyl-terminated polydimethylsiloxane, 25 parts of viscosity 30000mPa · s of vinyl-terminated polydimethylsiloxane, 30 parts of hydrogen-containing silicone oil with a hydrogen content of 0.9%, 15 parts of functionalized low-melting-point glass powder, and 4.5 parts of functionalized hexagonal boron nitride were placed in a planetary stirring kettle, the cold circulation system was turned on, the rubber temperature was controlled at 16°C, and the rubber was stirred at a speed of 1500 rad / min for 25 minutes to obtain base rubber B.

[0113] Step (3) transfer the base rubber B to the base rubber A, start the cold circulation system, stir at a speed of 5000 rad / min for 100 s, transfer to the mold, vulcanize at room temperature for 10 min, put into an oven, and vulcanize in the second stage at 62°C for 1.5 h to obtain ablation-resistant, high-efficiency, heat-insulating room temperature vulcanized silicone rubber foam.

[0114] Example 9.

[0115] Vinyltrimethoxysilane coupling agent is used to graft montmorillonite, kaolin, wollastonite and halloysite in a weight ratio of 1:1:1:1 to obtain a functionalized ceramic filler: 0.3 parts of vinyltrimethoxysilane coupling agent is added to a 75% ethanol aqueous solution, the temperature is controlled at 75°C, and the pH is adjusted to 3.5 with glacial acetic acid to fully hydrolyze the silane coupling agent; then 2 parts of montmorillonite, 2 parts of kaolin, 2 parts of wollastonite and 2 parts of halloysite are added, and after treating for 5.5 hours, the pH is adjusted to 9.4 with aqueous ammonia, and the mixture is washed with ethanol and dried to obtain a functionalized ceramic filler.

[0116] Glass powder with a melting point of 380°C is grafted with vinyl tri(β-methoxyethoxy) silane coupling agent to obtain functionalized low-melting-point glass powder: 0.3 parts of vinyl tri(β-methoxyethoxy) silane coupling agent is added to a 75% ethanol aqueous solution, the temperature is controlled at 75°C, the pH is adjusted to 3.5 with glacial acetic acid, and the silane coupling agent is fully hydrolyzed; then 10 parts of glass powder are added, and after treating for 5.5 hours, the pH is adjusted to 9.4 with ammonia water, and the solution is washed with ethanol and dried to obtain functionalized low-melting-point glass powder.

[0117] The hexagonal boron nitride was treated at 1080° C. for 1 hour, cooled and then washed with deionized water to obtain hydroxyl-modified hexagonal boron nitride.

[0118] Functionalized hexagonal boron nitride is obtained by grafting hydroxyl-modified hexagonal boron nitride with vinyl trimethoxy silane coupling agent: 0.1 parts of vinyl trimethoxy silane coupling agent are added to 75% ethanol aqueous solution, the temperature is controlled at 75°C, the pH is adjusted to 3.5 with glacial acetic acid, and the silane coupling agent is fully hydrolyzed; then 4 parts of hydroxyl-modified hexagonal boron nitride are added, and after treating for 5.5 hours, the pH is adjusted to 9.4 with ammonia water, and the solution is washed with ethanol and dried to obtain functionalized hexagonal boron nitride.

[0119] Mix 11 parts of Span 80 with 100 parts of a 35000 mPa · s hydroxyl-terminated polydimethylsiloxane is mixed, heated in a water bath to dissolve and mix evenly, and then 60 parts of glass powder with a melting point of 820°C, 10 parts of montmorillonite and 20 parts of the prepared hydroxyl-modified hexagonal boron nitride are added and continued to mix evenly to obtain a ceramic emulsion foaming agent.

[0120] Prepare ablation-resistant, high-efficiency, thermal-insulating room temperature vulcanized silicone rubber foam as follows:

[0121] Step (1) 50 parts of a 15000 mPa · s of hydroxyl-terminated polydimethylsiloxane, 22 parts of viscosity 50000mPa · s vinyl-terminated polydimethylsiloxane, 1.3 parts of 2400 ppm Castaplatin catalyst C 24 H 54O3PtSi6, 0.1 part of inhibitor, 5.5 parts of ceramic emulsion foaming agent, 8 parts of functionalized ceramic filler, and 2 parts of heat-resistant additive Al2O3 were placed in a planetary stirring kettle, the cold circulation system was turned on, the rubber temperature was controlled to 15°C, and the speed was 1400 rad / min for 24 minutes to obtain base rubber A. The inhibitor is a silicene compound with the structural formula: Among them, R 1 and R 2 Ethyl, R 3 R is methyl and R is isopropyl.

[0122] Step (2) 50 parts of a 15000 mPa · s of hydroxyl-terminated polydimethylsiloxane, 20 parts of viscosity 20000mPa · s of vinyl-terminated polydimethylsiloxane, 28 parts of hydrogen-containing silicone oil with a hydrogen content of 0.7%, 10 parts of functionalized low-melting-point glass powder, and 4 parts of functionalized hexagonal boron nitride were placed in a planetary stirring kettle, the cold circulation system was turned on, the rubber temperature was controlled at 20°C, and stirred at a speed of 1600 rad / min for 24 minutes to obtain base rubber B.

[0123] Step (3) transfer the base rubber B to the base rubber A, start the cold circulation system, stir at a speed of 4800 rad / min for 80 seconds, transfer to the mold, vulcanize at room temperature for 12 minutes, put into an oven, and vulcanize at 60°C for 2 hours to obtain ablation-resistant, high-efficiency, heat-insulating room temperature vulcanized silicone rubber foam.

[0124] Comparative Example 1.

[0125] The 5 parts of ceramic emulsion foaming agent in step (1) of Example 1 were replaced by 1.1 parts of glass powder with a melting point of 900° C., 0.8 parts of montmorillonite and 0.3 parts of hydroxyl-modified hexagonal boron nitride. The other process conditions and parameters were the same as those in Example 1.

[0126] Comparative Example 2.

[0127] The three parts of functionalized low-melting-point glass powder in step (2) of Example 1 were replaced by three parts of glass powder with a melting point of 900° C. The other process conditions and parameters were the same as those in Example 1.

[0128] Comparative Example 3.

[0129] 40 parts of glass powder with a melting point of 900° C. in the ceramic emulsion foaming agent in Example 1 were replaced with 40 parts of glass powder with a melting point of 500° C. Other process conditions and parameters were the same as those in Example 1.

[0130] Comparative Example 4.

[0131] The three parts of functionalized ceramic fillers in step (1) of Example 1 were replaced by three parts of montmorillonite, and the one part of functionalized hexagonal boron nitride in step (2) was replaced by one part of hexagonal boron nitride. The other process conditions and parameters were the same as those in Example 1.

[0132] Comparative Example 5.

[0133] The pouring order in step (3) of Example 1 was changed to transferring rubber material A to rubber material B, and stirring was carried out at a rotation speed of 1000 rad / min for 2 min. Other process conditions and parameters were the same as those in Example 1.

[0134] Comparative Example 6.

[0135] The hydroxyl-modified hexagonal boron nitride is removed from the ceramic emulsion foaming agent in Example 1, and the functionalized hexagonal boron nitride is removed in step (2). Other process conditions and parameters are the same as those in Example 1.

[0136] The samples of Examples 1-9 and Comparative Example 2 were tested, and the thickness of the tested samples was 20 mm. After being attacked by a 1300°C butane flame for 30 minutes, the samples of Examples 1-9 still had a complete structure, excellent thermal insulation effect, and the back temperature was maintained at about 170°C, while the Comparative Example was not assembled in situ by the filler, and the samples could not form a complete ceramic structure when attacked by the flame, and the back temperature reached 450°C.

[0137] The foam material performance was tested in accordance with national standards, including: apparent density test standard GB / T6343-2009, flame retardant performance test standard ISO4589-2:1996, LOI test standard GB / T10707-2008, ceramic body compression strength test standard GB / T1039-92, closed cell rate test standard GB / T10799-2008. The test results are shown in the table below.

[0138] <![CDATA[Apparent density (g / cm 3 )]]> Flame retardant properties LOI(%) Ceramic body compressive strength (MPa) Closed cell rate (%) Example 1 0.21 V0 29.5 5.0 95 Example 2 0.24 V0 30.1 5.1 93 Example 3 0.19 V0 30.4 4.5 96 Example 4 0.20 V0 29.8 4.8 94 Example 5 0.25 V0 31.2 4.6 93 Example 6 0.22 V0 31.4 4.9 95 Example 7 0.22 V0 30.6 4.7 94 Example 8 0.21 V0 30.2 5.0 93 Example 9 0.23 V0 31.0 4.6 95 Comparative Example 1 0.35 V1 25.4 3.1 78 Comparative Example 2 0.22 V1 26.1 2.9 90 Comparative Example 3 0.20 V1 25.6 3.3 92 Comparative Example 4 0.25 V1 26.5 3.5 85 Comparative Example 5 0.32 V1 24.8 2.7 81 Comparative Example 6 0.19 V0 29.1 1.8 91

Claims

1. Ablation-resistant, highly efficient, heat-insulating, room temperature vulcanized silicone rubber foam, characterized in that: The invention comprises the following components for blending and foaming, in parts by weight: The functionalized ceramic filler is obtained by grafting the ceramic filler with a silane coupling agent; The functionalized low-melting-point glass powder is obtained by grafting low-melting-point glass powder with a silane coupling agent, and the melting point of the low-melting-point glass powder is 350-600°C; The functionalized hexagonal boron nitride is obtained by grafting hydroxyl groups onto the hexagonal boron nitride using a silane coupling agent; The ceramicizable emulsion foaming agent is a mixture of the following substances, measured in parts by weight: The ceramic filler is one or more of montmorillonite, kaolin, wollastonite and halloysite; the hydroxyl-modified hexagonal boron nitride is obtained by treating hexagonal boron nitride at high temperature and washing with deionized water after cooling, and the high temperature is 900-1200°C.

2. The ablation-resistant, high-efficiency, heat-insulating, room-temperature-vulcanized silicone rubber foam according to claim 1, characterized in that: The viscosity of the vinyl-terminated polydimethylsiloxane is 20,000 to 50,000 mPa. · s; The hydrogen content of the hydrogen-containing silicone oil is 0.5-1.6%.

3. The ablation-resistant, high-efficiency, heat-insulating, room-temperature-vulcanized silicone rubber foam according to claim 1, characterized in that: The catalyst is a Castaplatin catalyst, the chemical formula of which is C 24 H 54 O3PtSi6, concentration is 2000~5000ppm.

4. The ablation-resistant, high-efficiency, heat-insulating, room-temperature-vulcanized silicone rubber foam according to claim 1, characterized in that: The inhibitor is a silicene compound with the structural formula: Among them, R 1 , R 2 and R 3 are H, methyl or ethyl respectively, and R is cyclohexyl or isopropyl.

5. The ablation-resistant, high-efficiency, heat-insulating, room-temperature-vulcanized silicone rubber foam according to claim 1, characterized in that: The silane coupling agent is vinyl triethoxy silane, vinyl trimethoxy silane or vinyl tri (β-methoxyethoxy) silane.

6. The ablation-resistant, high-efficiency, heat-insulating, room-temperature-vulcanized silicone rubber foam according to claim 1, characterized in that: The heat-resistant additive is one or more of SnO2, Fe2O3, CeO2, and Al2O3.

7. The ablation-resistant, high-efficiency, heat-insulating, room-temperature-vulcanized silicone rubber foam according to claim 1, characterized in that: The emulsifier is one or more of Span 20, Span 60 and Span 80; the melting point of the high melting point glass powder is 650-900°C; The emulsifier and hydroxyl-terminated polydimethylsiloxane are mixed, heated in a water bath to dissolve and mix evenly, and then high melting point glass powder, ceramic filler and hydroxyl-modified hexagonal boron nitride are added and mixed evenly to obtain a ceramic emulsion foaming agent.

8. A method for preparing the ablation-resistant, high-efficiency, heat-insulating, room-temperature-vulcanized silicone rubber foam according to any one of claims 1 to 7, characterized in that: Step (1) Weigh 50 parts by weight of hydroxyl-terminated polydimethylsiloxane, 10 to 30 parts by weight of vinyl-terminated polydimethylsiloxane, 0.4 to 1.5 parts by weight of a catalyst, 0.1 to 0.5 parts by weight of an inhibitor, 5 to 10 parts by weight of a ceramic emulsion foaming agent, 3 to 15 parts by weight of a functionalized ceramic filler, and 1 to 3 parts by weight of a heat-resistant additive, place the mixture in a planetary stirring kettle, start a cold circulation system, control the temperature of the rubber material to be 15 to 25° C., and stir at a speed of 1000 to 2000 rad / min for 20 to 30 minutes to obtain a base rubber A; Step (2) Weigh 50 parts by weight of hydroxyl-terminated polydimethylsiloxane, 10 to 30 parts by weight of vinyl-terminated polydimethylsiloxane, 20 to 40 parts by weight of hydrogen-containing silicone oil, 3 to 15 parts by weight of functionalized low-melting-point glass powder, and 1 to 5 parts by weight of functionalized hexagonal boron nitride, place them in a planetary stirring kettle, start a cold circulation system, control the temperature of the rubber material to 15 to 25° C., and stir at a speed of 1000 to 2000 rad / min for 20 to 30 min to obtain a base rubber B; Step (3) transfer the base rubber B to the base rubber A, start the cold circulation system, stir at a speed of 4000-6000 rad / min for 1-2 min, transfer to the mold, vulcanize at room temperature for 10-20 min, put into an oven, and vulcanize in two stages at 60-80° C. for 1-2 h to obtain ablation-resistant, high-efficiency, heat-insulating, room-temperature vulcanized silicone rubber foam.

Citation Information

Patent Citations

  • Room temperature vulcanized ceramicized silicone rubber foam sealant and its preparation method

    CN108219473B

  • Ablation-resistant efficient heat-insulating room-temperature vulcanized silicone rubber foam and preparation method thereof

    CN115044210A